Telemedicine On The Growth of Law-Based Industries in Indonesia - Bella Armeda Aprilia; Arief Suryono (International Forum of Researchers and Lecturers, 2024)
The digital transformation of telemedicine is a new innovation in the field of medical services with the characteristics of technology, proliferation of computers and automation, community involvement. Interpretive analysis using a conceptual approach and a legislative approach found that the digital transformation of telemedicine has the potential to increase the quality of medical services but is diametrically opposed to the complexity of medical service values which must then be anticipated so that there is no degradation of human values in the health industry. In line with the development of the health industry and to answer the needs for medical services in society, legal construction is needed that functions as a means of protection for health service providers and patients as recipients of health services. The recommended legal construction is: revising legislation related to medical practice by providing proportional legal protection for doctors and patients at the level of telemedicine history taking and diagnosis, as well as the use of recordings as evidence in resolving telemedicine digital transformation disputes. This is intended so that the development of medical practice technology is in accordance with the principles of Pancasila which are based on scientific values, benefits, justice, humanity, balance, as well as patient protection and safety.